2016
DOI: 10.1109/jstars.2016.2533662
|View full text |Cite
|
Sign up to set email alerts
|

Geostationary Image Simulation on Coastal Waters Using Hydrodynamic Biogeochemical and Sedimentary Coupled Models

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…They showed that the sun zenith angle variation is not considered to be a major cause of the error in the estimation of SPM concentration up to a very high sun zenith angle (typically greater than 70°). Simulations by Lei et al [31] showed that the solar angle variation could have a greater impact on chlorophyll estimation (53%) than SPM estimation (5%).…”
Section: B Goci Satellite Datamentioning
confidence: 99%
“…They showed that the sun zenith angle variation is not considered to be a major cause of the error in the estimation of SPM concentration up to a very high sun zenith angle (typically greater than 70°). Simulations by Lei et al [31] showed that the solar angle variation could have a greater impact on chlorophyll estimation (53%) than SPM estimation (5%).…”
Section: B Goci Satellite Datamentioning
confidence: 99%
“…Both the absorption and backscattering coefficient of TSM are significantly elevated with increasing sediment, which makes it possible to construct relationships between TSM and the remote sensing signal. Over the past several decades, an increasing number of studies based on analytical, empirical and semi-analytical methods have mapped TSM concentrations with satellite data around the world [7][8][9][10][11][12][13]. The analytical models in these studies were based on strict theoretical derivation, which tends to be more applicable for different water types than empirical models.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the radiative transfer theory, Lee, et al [26] gave a theoretical explanation of a p (λ) and b bp (λ) and then established a quasi-analytical algorithm (QAA) for relating a p (λ) and b bp (λ) to multiband surface reflectance for ocean and coastal environments. Many subsequent works have presented applications of the QAA model in deriving a p (λ) as well as b bp (λ) from remote sensing reflectance and, consequently, for estimating the surface TSM concentration in different water types [11][12][13]. The semianalytical methods allow insights on the process themselves and provide a representation of the current water condition that is consistent with the governing physical processes [9,10].…”
Section: Introductionmentioning
confidence: 99%